Youtube as Da'wah Media Innovation in Disruption Era - Mustofa Hilmi (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
This article aims to analyze YouTube as a da'wah media for Muslim preachers in the disruption era. The use of Youtube as a medium of preaching significantly impacted developing increasingly competitive digital da'wah content. The digitalization of Islamic da'wah on Youtube has made the Dai (preacher) more proactive in making updates and adjustments. Dai's proficiency in the mastery of dakwah media via Youtube is one of the determining factors in digitizing da'wah. Therefore, Dai, who uses Youtube as a medium of preaching in the digital era, must always carry out innovation. Dai can create material videos by adding stimulating effects such as animated visualization, adding unique descriptions for important material points, and religious music back sounds. Dai also take advantage of image editing applications such as CorelDRAW, Photoshop, and video applications such as Filmora, VideoPad, or Adobe Premiere in the material creation process. Innovation is the process of making a da'wah video is very important so that the da'wah material can touch the community, especially the millennial generation.